Parvoviral infection with systemic impact and renal consequences. Issue 6 (8th June 2019) - Mira, Filipe Santos; Marques, Daniel; Sousa, Vítor; Nogueira, Célia; Garcia, Rui; Alves, Rui
Abstract : Parvovirus infection is usually asymptomatic especially in immunocompetent adults. When symptomatic it can range from mild to life threatening depending on the patient's age and comorbidities. We report a case of a 40-year-old male patient with parvovirus infection who presented a purpuric rash in distal extremities, acute kidney injury, type II mixed cryoglobulinaemia and hypocomplementaemia. His renal biopsy showed a mesangioproliferative glomerulonephritis with positive immunoreactivity to C3, IgM and C1q. Parvovirus B19 was detected in the biopsy tissue by PCR. He was treated with prednisolone with total remission after 1 month. We discuss the diagnosis of kidney lesion due to parvovirus in an immunocompetent person, which is a very rare condition and its association with the cryoglobulinaemia diagnosis.